2006
DOI: 10.1007/bf02773825
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotics for Amitsur's Capelli-type polynomials and verbally prime PI-algebras

Abstract: We consider associative P I-algebras over a field of characteristic zero. The main goal of the paper is to prove that the codimensions of a verbally prime algebra [11] are asymptotically equal to the codimensions of the T -ideal generated by some Amitsur's Capelli-type polynomials E *

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In [3] this result was extended to finite dimensional simple superalgebras and in [6] the authors found similar result in the case of algebras with involution (for a survey see [7]). The link between the asymptotic of the codimensions of the Amitsur's Capelli-type polynomials and the verbally prime algebras was studied in [5].…”
Section: Introductionmentioning
confidence: 99%
“…In [3] this result was extended to finite dimensional simple superalgebras and in [6] the authors found similar result in the case of algebras with involution (for a survey see [7]). The link between the asymptotic of the codimensions of the Amitsur's Capelli-type polynomials and the verbally prime algebras was studied in [5].…”
Section: Introductionmentioning
confidence: 99%
“…., which is an important numerical characteristic of polynomial identities of A. Study of asymptotic behavior of {c n (A)} for associative algebras was started in the beginning of 70's (see, for example, [23], [15], [16]) and was continued during the subsequent decades (see, for example, [14], [6], [10], [3], [4], [5], [24] and also the bibliography in [11]). Later, similar numerical characteristics were considered for Lie algebras [17], [25], [18] and other non-associative algebras: Lie superalgebras [28] and their generalizations [22], Leibniz algebras [21], Jordan and alternative algebras [12], [9], Poisson and Novikov algebras [20], [8], etc.…”
Section: Introductionmentioning
confidence: 99%
“…In [4] these result was extended to finite dimensional simple superalgebras proving that the graded codimensions of the T 2 -ideal generated by the graded Capelli polynomials Γ M+1,L+1 , for some fixed M , L, are asymptotically equal to the graded codimensions of a simple finite dimensional superalgebra. The link between the asymptotic of the codimensions of the Amitsur's Capelli-type polynomials and the verbally prime algebras was studied in [5].…”
Section: Introductionmentioning
confidence: 99%